PHYSICAL AND MATHEMATICAL SIMULATION OF FRETTING-CORROSION PROCESS OF GAS-THERMAL COATINGS - I. O. Sokorov; N. V. Spiridonov (Наука и техника)
The paper presents a physical and mathematical simulation of wearing-out process of gas-thermal coatings at fretting-corrosion effect. The given simulation allows to take into account influence of the environment, working conditions of parts and also influence of physical and mechanical properties and tribo-technical characteristics of gas-thermal coatings on their wearing-out under fretting-corrosion conditions.